Evaluation of sorption properties of biochar produced by hydrothermal liquefaction of Phragmites australis - Natalia A. Muravieva; Yuliya V. Kulikova; Olga O. Babich (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to use an innovative method of thermochemical conversion of wet biomass and organic waste – hydrothermal liquefaction. This paper focuses on the further application of the by-product of the process – solid coal residue (biochar). The obtained solid residue is proposed to be used as sorbent. Aim. To evaluate the sorption capacity of carbon residues from hydrothermal liquefaction of common reed, as well as to select methods for their activation. Object. Hydrochar produced by hydrothermal liquefaction from plant biomass – common reed (Phragmites australis). Methods. Hydrothermal liquefaction, chemical activation of hydrochar sorbents by hydrogen peroxide and vapor-gas activation, sorption capacity by methylene blue, elemental analysis, specific surface area measurement by the Brunaer, Emmett and Teller method, nitrogen sorption–desorption at 77 K. Results. Sorbent yield during activation was 45 and 30% with chemical activation and 91% with steam-gas activation. The maximum sorption capacity for methylene blue of 18.4 mg/g was achieved due to chemisorption for the sample after carbon activation with peroxide in the presence of sulphuric acid. The maximum BET surface area (18.47 m2/g) and total pore volume (0.186 cm3/g) were achieved for the sample after gas-vapor activation. Based on the results of porous structure evaluation, the mesoporous structure of the obtained coals was discovered. The obtained coals showed sorption properties as good as those of similar cheap waste sorbents. The authors have proved the possibility of using the obtained sorbents for solving environmental problems, including wastewater treatment.